Occurrence and Molecular Characteristics of Extended-Spectrum Beta-Lactamase-Producing Enterobacterales Recovered From Chicken, Chicken Meat, and Human Infections in Sao Paulo State, Brazil - Cardozo, Marita Vedovelli; Liakopoulos, Apostolos; Brouwer, Michael; Kant, Arie; Pizauro, Lucas José Luduvério; Borzi, Mariana Monezi; Mevius, Dik; de Ávila, Fernando Antonio (Frontiers in Microbiology, 2021)
This study aimed to investigate the phylogenetic diversity and epidemiology of ESBL-producing Escherichia coli and Klebsiella pneumoniae from chicken, chicken meat and human clinical isolates in Sao Paolo state, Brazil, and characterize their respective ESBL-encoding plasmids. Three hundred samples from chicken cloaca, chicken meat and clinical isolates were phenotypically and genotypically assessed for extended-spectrum beta-lactamase (ESBL) resistance. Isolates were identified by MALDITOF-MS and further characterized by MLST analysis and phylogenetic grouping. ESBL genes were characterized and their location was determined by S1-PFGE and Southern blot, conjugation, transformation, and PCR-based replicon typing experiments. Thirty-seven ESBL-producing isolates (28 E. coli and 9 K. pneumoniae) that were positive for the blaCTX-M-1 or blaCTX-M-2 gene groups were obtained. Two isolates were negative in the transformation assay and the chromosomal location of the genes was deduced by Southern blot. The blaCTX-M genes identified were carried on plasmid replicon-types X1, HI2, N, FII-variants, I1 and R. The E. coli isolates belonged to nine sequence types while the K. pneumoniae isolates belonged to four sequence types. The E. coli isolates belonged to phylotype classification groups A, B1, D and F. This study demonstrated that isolates from cloacal swabs, chicken meat and human feces had genetic diversity, with a high frequency of blaCTX-M-15 among chickens, chicken meat and human feces. Thus, this reinforce the fact that chickens, as well as their by-products, could be an important source of transmission for ESBL-producing pathogens to humans in South America.